Immersive Audio Podcast Episode 93 (Jürgen Herre, MPEG-I) - Herre, Jürgen (2023)
In this episode of the Immersive Audio Podcast, Oliver Kadel and Monica Bolles are joined by the Chief Executive Scientist for Audio and Multimedia fields at Fraunhofer International Audio Laboratories – Juergen Herre from Erlangen, German
### Other Presentations